Field‐based mechanical phenotyping of cereal crops to assess lodging resistance. (16th August 2020) - Erndwein, Lindsay; Cook, Douglas D.; Robertson, Daniel J.; Sparks, Erin E.
Abstract : Plant mechanical failure, also known as lodging, is the cause of significant and unpredictable yield losses in cereal crops. Lodging occurs in two distinct failure modes—stalk lodging and root lodging. Despite the prevalence and detrimental impact of lodging on crop yields, there is little consensus on how to phenotype plants in the field for lodging resistance and thus breed for mechanically resilient plants. This review provides an overview of field‐based mechanical testing approaches to assess stalk and root lodging resistance. These approaches are placed in the context of future perspectives. Best practices and recommendations for acquiring field‐based mechanical phenotypes of plants are also presented.